RELEVANSI NILAI-NILAI PANCASILA TERHADAP RANAH PENDIDIKAN SEBAGAI PENGUAT KETERAMPILAN DI ABAD 21 - Syam, Christanto; Olendo, Yudhistira Oscar; Putra, Zakarias Aria Widyatama; Dewantara, Jagad Aditya (Academy of Education Journal, 2023)
Being a deep linkage of morals formed from Pancasila values can also be connected to the realm of education and become a bridge in its efforts to strengthen skills in the 21st century. Whereas 21st century skills produce learner competency outcomes to navigate changes in civilization, being a paradigm of Pancasila values can counteract the negative impacts resulting from individualistic attitudes due to inaction in implementing 21st century skills. This research uses a qualitative method with a case study approach. This research uses a qualitative method with a case study approach. The data sources used verbal and nonverbal data sources. Data collection methods used observation, interviews, and documentation. Data analysis in this research is using the interactive model of Miles and Huberman. Reliability and validity of data in this qualitative research used trust test and focused on triangulation techniques.Pancasila values have relevance to the realm of education in the cognitive, affective, and psychomotor domains. The values of Pancasila can also strengthen skills in the 21st century The relevance of Pancasila values to the realm of education as a strengthener of skills in the 21st century is certainly interrelated. This is to dismiss concerns in responding to the growing civilization. The values of Pancasila become the foundation in the realm of education so that, it can complete the domain in Bloom's taxonomy in learning. Meanwhile, 21st century skills will be strong with the relevance that exists between the values of Pancasila and the realm of education.